Pavement Diagnosis as Integrant of the Pavement Management System - Jan Celko; Martin Decky; Jozef Komacka; Matus Kovac (Communications - Scientific letters of the University of Zilina, 2008)
The paper integrates the most important scientific information of the authors in the field of diagnostics of road pavements. Basic attributes of pavement serviceability (evenness, skid resistance) and pavement bearing capacity are the core of the paper. The results of simulations of dynamic systems, outputs of the models developed at the authors place, the correlations to the world established parameters of evenness and skid resistance are presented in the paper. Objective scientific outputs have formed an effectual base for development the Slovak Pavement Management System (PMS). The principles of the Slovak PMS are described.